The 3D printing technology and its disruptions in the supply chain - Cubillos Cuéllar, Laura Daniela
3D printing technology is generating severe disruptions in global supply chains. This technology undermines the sense of longdistance transport, decentralizes production sites, approaches demand, personalizes it, influences the needs of last-mile transport, changes the requirements established in the logistics service of the future. Directly affecting the traditional logistics between suppliers and retailers, since the processes will be executed in a single installation, and the orders will arrive directly from the factory to the consumer. It will potentially reduce storage, shipping -distribution-, and increase mass product customization; the old large-scale production and the labor sector will face a strong impact due to the control in the consumption of raw materials, absence of assembly lines and optimization of inventory management; manufacturing an item will be more in the hands of consumers, which means that the supply chain will be customized. 3D printing is a disruptive technology that will radically change the structures of global supply chains as we know them today.